Multikulturalisme dalam Konsep Kurikulum Pendidikan Agama Islam (Landasan Filsafat Pendidikan Islam) - Aulia, Ridha; Fathunnajih, Fathunnajih; Br, Budiman; Mutmainnah, Inayatul; Ghazali, Al; Rusmayadi, Rusmayadi (Asatiza: Jurnal Pendidikan, 2024)
An undeniable fact that still often occurs in Indonesia is friction between religions in the community. The root of the problem is because people do not understand the concept of Multicultural, so it is important for Religious Learning to include this value in the curriculum. The purpose of writing this article is to find out the philosophical basis in multicultural education and its relevance to Islamic Religious Education, as well as its application in educational institutions today. The type of research applied in this article is a literature study with descriptive qualitative methods. The conclusion of this research is that the philosophical basis used in multicultural education is not timeless with the concept of Indonesian statehood, multicultural education is a concept that is very relevant to religious values, in its application it has been implemented through the concept of the 2013 curriculum.